Structured Personalized Oxygen and Supportive Therapies for Dyspnea in Oncology (SPOT-ON): A personalized randomized clinical trial protocol - David Hui; Min Ji Kim; Saji Thomas; Gautam Sachdev; Sanjay Shete; Nisha Rathi; Nicole Hensch; Vera De La Cruz; Amy Ontai; Donald A. Mahler; Jie Li; Eduardo Bruera (PLoS ONE, 2025)
Background Low-flow supplemental oxygen (LFSO), high-flow nasal cannula (HFNC), and non-invasive ventilation (NIV) are often used for palliation of dyspnea in hospitalized patients. However, it is unclear how patients prefer to use these modalities and how they can be personalized for optimal dyspnea relief. The objective of this randomized clinical trial is to compare the effect of a personalized respiratory therapist (RT)-led intervention, termed SPOT-ON, and enhanced usual care on dyspnea intensity in both hypoxemic and non-hypoxemic hospitalized patients with cancer. Methods In this two-arm, parallel group, partially blinded, waitlist-controlled randomized clinical trial, hospitalized patients with advanced cancer and at least moderate dyspnea intensity at rest (numeric rating scale [NRS] ≥4/10) will be randomized 1:1 to receive SPOT-ON immediately or after a 72-hour waiting period. The SPOT-ON intervention consists of a time-limited trial of LFSO, HFNC, and NIV for 10 minutes each, followed by personalized deployment of these modalities to tailor device settings and timing and duration of use based on patient preference over 72 hours. The waitlist control group will receive structured dyspnea education after enrollment and usual care. The primary outcome will be change in dyspnea NRS intensity from baseline to 24 hours. Secondary outcomes include dyspnea unpleasantness, vital signs, symptom burden, health-related quality of life, adverse events, pattern of device use, and hospital outcomes. We calculated that 150 patients (75 hypoxemic and 75 non-hypoxemic) will provide 80% power to detect a 1.2-point difference between groups with α = 0.025, assuming a standard deviation of 1.5 and 20% attrition. Discussion Successful completion of this clinical trial could inform the use of oxygen and supportive modalities to reduce dyspnea. This novel personalized clinical trial methodology involving time-limited trials to tailor therapy based on patient preferences may inform the design of future supportive care clinical trials. Trial registration Clinicaltrials.gov NCT06336642